2000
DOI: 10.1107/s0108270100007514
|View full text |Cite
|
Sign up to set email alerts
|

O-IsopropylN-(2-furoyl)thiocarbamate

Abstract: The title compound, C(9)H(11)NO(3)S, has crystallographic mirror symmetry, occurs in the thiocarbamate form and is stabilized in an s-cisoid,s-transoid conformation with respect to the C-N-C group. There are two intramolecular hydrogen bonds, one between the H atom of the N-H group and the O atom of the furan ring, and the other between the H atom of the secondary carbon of the isopropyl group and the S atom. The packing of the molecules is assumed to be dictated by van der Waals interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…A similar E-conformation is found in the structure of iPrOC(LS)N(H)R9, where R9 is 2-furoyl. 14 However, in this case the { … H-N-CLS} 2 synthon is not observed owing to the presence of intramolecular N-H … O and C-H … S bonds. Similarly, in the structures of ROC(LS)N(H)R9, where R 5 Me and Et, and R9 is 2,3,4,6tetra-O-acetyl-b-D-glucopyranosyl, 15 and MeOC(LS)N(H)R9, where R9 is 2-(2-methyl-5-nitro-1H-imidazol-1-yl), 16 the {RC(LS)N(R)H)} 2 synthon is absent owing to the presence of intermolecular N-H … O interactions.…”
Section: Introductionmentioning
confidence: 87%
“…A similar E-conformation is found in the structure of iPrOC(LS)N(H)R9, where R9 is 2-furoyl. 14 However, in this case the { … H-N-CLS} 2 synthon is not observed owing to the presence of intramolecular N-H … O and C-H … S bonds. Similarly, in the structures of ROC(LS)N(H)R9, where R 5 Me and Et, and R9 is 2,3,4,6tetra-O-acetyl-b-D-glucopyranosyl, 15 and MeOC(LS)N(H)R9, where R9 is 2-(2-methyl-5-nitro-1H-imidazol-1-yl), 16 the {RC(LS)N(R)H)} 2 synthon is absent owing to the presence of intermolecular N-H … O interactions.…”
Section: Introductionmentioning
confidence: 87%
“…[53][54][55][56][57][58][59][60][61][62][63][64][65] In one structure, Oisopropyl N-(2-furoyl)thiocarbamate, intramolecular N-H/S and N-H/O (derived from the 2-furoyl ring) contacts preclude intermolecular association via N-H/S. 66 The final example of a molecule with an E-conformation presents a unique example where there are two independent molecules in the crystallographic asymmetric unit of O-benzyl N-((2-furyl)carbonyl)thiocarbamate. One molecule has an E-conformation and the other has a Z-conformation.…”
Section: Database Surveymentioning
confidence: 99%
“…1 and selected geometric parameters are collected in Table 1 parameters precludes any definitive trends to be discerned in the bond distances across the series except to mention that each of the structures exists in the thione form, as illustrated in Scheme 1. Nevertheless, the C1-N1 bond distances, which range from 1.312(2) A ˚(3) to 1.3231(17) A ˚(2), are indicative of some delocalization of p-electron density in the C1-N1 bonds and, accordingly, the conformations of the molecules may be ascribed as E. Indeed, E-conformations are normally found in O-alkyl-N-aryl-thiocarbamides [20][21][22][23][24][25][26][27] and a recent theoretical study showed that E-conformations were favoured over Z-conformations by about 5 kJ mol 21 . 26 An expected consequence of an E-conformation is the facile formation of the { … H-N-CLS} 2 , thioamide, synthons and this is found in each of 1-3 as shown in Fig.…”
Section: Molecular Structuresmentioning
confidence: 99%
“…However, in keeping with the notion that hydrogen-bonding synthons are not as prevalent owing to competing synthons, 9 there is one example of an O-alkyl-N-aryl-thiocarbamide structure with an E-conformation that does not associate via a { … H-N-CLS} 2 synthon. 22 Further, there are several structures where Z-conformations are found. 26,[28][29][30] The appearance of these has been rationalised in terms of competing supramolecular synthons that dominate the crystal packing and which are of sufficient energy to overcome the normal preference of E-over Z-conformations.…”
Section: Molecular Structuresmentioning
confidence: 99%